ADAPTASI SPASIAL PADA INTERIOR RUMAH TINGGAL PASCA GEMPA DI KASONGAN BANTUL - Dwi Nugroho, Martino (Lintas Ruang: Jurnal Pengetahuan dan Perancangan Desain Interior, 2008)
May 27, 2006, was a somber day for the people living ini Yogyakarta and Central JavaProvinces. Sub-province of Bantul was the most severely hit by the earthquake happening earlyin the morning. Around 7.057 houses were sacked, including the craft village of Kasongan. Most Kasongan families now live in houses made avalaible by domestic and foreign aids. They have lived in the new houses for two years. During this time, they have to make adjusments to the new environment. This research is intended to observe how families living at the village of Kajen, Kasongan, make adjustments and adapt to the new conditions living in new houses supplied through aids. This village is purposely chosen as the sample. The result of the investigation indicates that people of this village has to return the heat during the day, doing activities by usingmulti-purpose space and furniture.Keywords : interior, adaptation, adjustment.